The effects of a self‐management treatment package on daily step count in university students with depressive symptoms. (4th November 2022) - Munno, Reghann K.; Thomson, Kendra M.; Zonneveld, Kimberley L. M.
Abstract: Research demonstrates that exercise can decrease depressive symptoms, yet it is infrequently prescribed as an intervention. Self‐management techniques offer an effective and cost‐efficient approach to increase engagement in physical activity. The purpose of this study was to evaluate the efficacy of goal setting, self‐monitoring, and feedback for increasing daily step count in university students ( N  = 4) reporting depressive symptoms. The treatment was efficacious for increasing steps for three participants with varying levels of consistency. All participants showed a decrease in some depression symptoms on the University Student Depression Inventory. Expert ratings on the Clinical Global Impression Scale indicated improvement in global functioning for three participants. Additional research is needed to determine the efficacy of this intervention package for increasing daily steps and the relation to depression symptoms.